Evaluating the Use of Smartwatches for Learning Purposes through the Integration of the Technology Acceptance Model and Task-Technology Fit. Issue 19 (26th November 2021) - Al-Emran, Mostafa
ABSTRACT: Despite the growing literature on employing smartwatches for communication and healthcare services, there is little debate on how to use these wearables for educational purposes. Therefore, this research develops a hybrid theoretical model through the integration of the Technology Acceptance Model (TAM), Task-technology Fit (TTF) variables, and the most quality features of smartwatches, namely availability and mobility in order to explore the students' behavioral intention to adopt smartwatches for learning activities. The developed model was validated through data collected from 275 university students using the partial least squares-structural equation modeling (PLS-SEM) technique. The empirical results indicated that individual-technology fit and task-technology fit positively impact the perceived usefulness of smartwatches, while no positive effects were reported on the ease of use of these wearables for educational purposes. The results also revealed that availability and mobility positively affect the perceived ease of use of smartwatches for instructional activities. The theoretical contributions and practical implications of these results were also tackled.